2018
DOI: 10.1007/978-3-030-00129-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Joint Motion Estimation and Segmentation from Undersampled Cardiac MR Image

Abstract: Accelerating the acquisition of magnetic resonance imaging (MRI) is a challenging problem, and many works have been proposed to reconstruct images from undersampled k-space data. However, if the main purpose is to extract certain quantitative measures from the images, perfect reconstructions may not always be necessary as long as the images enable the means of extracting the clinically relevant measures. In this paper, we work on jointly predicting cardiac motion estimation and segmentation directly from under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Segmentation can also be treated as a regression task [Tan et al, 2017]. Finally, temporal information related to the cardiac motion has been used for segmentation of all cardiac phases [Qin et al, 2018, Bai et al, 2018b. Differently from the above, in this work we focus on learning meaningful spatial representations, and leveraging these for improved semi-supervised segmentation results, and performing auxiliary tasks.…”
Section: Cardiac Segmentationmentioning
confidence: 99%
“…Segmentation can also be treated as a regression task [Tan et al, 2017]. Finally, temporal information related to the cardiac motion has been used for segmentation of all cardiac phases [Qin et al, 2018, Bai et al, 2018b. Differently from the above, in this work we focus on learning meaningful spatial representations, and leveraging these for improved semi-supervised segmentation results, and performing auxiliary tasks.…”
Section: Cardiac Segmentationmentioning
confidence: 99%
“…Deep Learning (DL) methods have demonstrated the advantage of allowing real-world data guide learning of abstract representations that can be used to accomplish pre-specified tasks, and have been shown to be more robust to image artifacts than non-learning techniques for some applications (16,17). DL segmentation methods have been proposed (18)(19)(20)(21) and implemented within strain computational pipelines (22,23), and recent studies have shown that cardiac motion estimation can also be recast as a learnable problem (24)(25)(26)(27)(28). These methods usually consist of an intensity-based loss function and a constrain term (24,27), the latter using common machine learning techniques [e.g., L2 regularization of all learnable parameters (25)] or direct regularization of the motion estimates [e.g., smoothness penalty (24), anatomy-aware (28)].…”
Section: Introductionmentioning
confidence: 99%
“…DL segmentation methods have been proposed (18)(19)(20)(21) and implemented within strain computational pipelines (22,23), and recent studies have shown that cardiac motion estimation can also be recast as a learnable problem (24)(25)(26)(27)(28). These methods usually consist of an intensity-based loss function and a constrain term (24,27), the latter using common machine learning techniques [e.g., L2 regularization of all learnable parameters (25)] or direct regularization of the motion estimates [e.g., smoothness penalty (24), anatomy-aware (28)]. However, none of these methods have considered the accuracy of myocardial strain as a design factor or have been applied to strain analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Lme is calculated based on the ground truth respiratory‐resolved images because the undersampling artefacts in the ZF bin images will influence the loss calculation. A similar strategy has been used in a previous study, which trained a network to predict 2D nonrigid cardiac motion from undersampled cardiac cine images 34 …”
Section: Methodsmentioning
confidence: 99%
“…A similar strategy has been used in a previous study, which trained a network to predict 2D nonrigid cardiac motion from undersampled cardiac cine images. 34…”
Section: Diffeomorphic Respiratory Motion Estimation Networkmentioning
confidence: 99%